2016
DOI: 10.4238/gmr.15038602
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, proliferation, and induction of Bama mini-pig spermatogonial stem cells in vitro

Abstract: ABSTRACT. Spermatogonial stem cells (SSCs), the unique seed cells of testes, can undergo meiosis and form spermatozoa, thus transmitting genetic information to offspring. Research concerning these cells explores the mechanism underlying spermatogenesis, making possible the induction of their differentiation into spermatozoa in vitro. SSCs have therefore attracted much interest among scientists. Although the proliferation of such cells in vitro has been demonstrated, we are unaware of any long-term laboratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…1). In 3 months old testes, type A spermatogonia (Zhao et al 2016). In 5 months old testis, DBA positive cells were located both in basement membrane and just next to the basement membrane.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1). In 3 months old testes, type A spermatogonia (Zhao et al 2016). In 5 months old testis, DBA positive cells were located both in basement membrane and just next to the basement membrane.…”
Section: Resultsmentioning
confidence: 92%
“…2). UCHL1 expression is restricted to spermatogonial stem cells of prepubertal bull (Herrid et al 2007, Reding et al 2010, cat (Vansandt 2014), prepubertal buffalo (Goel et al 2010) and porcine (Zhao et al 2016). However, in neonatal and adult bovine testis, UCHL1 is expressed in gonocytes and spermatogonia (Fujihara et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Porcine testicular cells were cultured in vitro and porcine SSC-like colonies could be maintained for 9 passages [ 17 ]. Previously, we reported that SSCs of Bama mini-pig could be maintained for up to 3 months on SIM mouse embryo derived thioguanine- and ouabain-resistant (STO) feeder layer [ 28 ]. However, the cultured SSCs were influenced by unknown factors from serum and feeder layer cells, and no previous report has provided evidence that long-term-cultured SSCs from pig can maintain spermatogenesis potential.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the SSCs was performed as our previous study (Zhao et al, ). Generally, the testes were obtained from 1 month Bama mini‐pigs at the farm and transported to the laboratory on ice.…”
Section: Methodsmentioning
confidence: 99%
“…The testes from 1 and 2 months pigs were subjected to immunohistochemical analysis. The staining process was performed as our previous report (Zhao et al, ). Briefly, the testes were cut into small pieces, fixed with Bouin's fixative for 12 hr at room temperature, dehydrated, embedded in paraffin and sectioned into slices (4 µm thick).…”
Section: Methodsmentioning
confidence: 99%